A refined model of body mass and population density in flightless birds reconciles extreme bimodal population estimates for extinct moa. Issue 3 (1st December 2019) - Latham, A. David M.; Latham, M. Cecilia; Wilmshurst, Janet M.; Forsyth, David M.; Gormley, Andrew M.; Pech, Roger P.; Perry, George L. W.; Wood, Jamie R.
Abstract : Flightless birds were once the largest and heaviest terrestrial fauna on many archipelagos around the world. Robust approaches for estimating their population parameters are essential for understanding prehistoric insular ecosystems and extinction processes. Body mass and population density are negatively related for extant flightless bird species, providing a method for quantifying densities and population sizes of extinct flightless species. Here we assemble an updated global data set of body mass and population densities for extant flightless birds and estimate the relationship between these variables. We use generalised least squares models that account for phylogenetic relatedness and incorporate the effects of limiting factors (e.g. habitat suitability) on population density. We demonstrate the applicability of this allometric relationship to extinct species by estimating densities for each of the nine species of moa (Dinornithiformes) and generating a combined spatially explicit map of total moa density across New Zealand. To compare our density estimates with those previously published, we summed individual species' abundances to generate a mean national density of 2.02–9.66 birds km −2 for low‐ and high‐density scenarios, respectively. Our results reconcile the extreme bimodality of previous estimates (< 2 birds km −2 and > 10 birds km −2 ) and are comparable to contemporary densities of large herbivorous wild mammals introduced into New Zealand about 150 yr ago. The revised moa density has little effect on the harvest rates required to bring about extinction within 150–200 yr, indicating that rapid extinction was an inevitable response to human hunting, irrespective of the initial population of moa.